External α-carbonic anhydrase and solute carrier 4 are required for bicarbonate uptake in a freshwater angiosperm. (28th July 2020) - Huang, Wenmin; Han, Shijuan; Jiang, Hongsheng; Gu, Shuping; Li, Wei; Gontero, Brigitte; Maberly, Stephen C
Abstract : Acquisition of bicarbonate (HCO3 – ) in Ottelia alismoide relies on co-diffusion of CO2 and HCO3 – through the boundary layer, conversion of HCO3 – to CO2 at the plasmalemma by α-carbonic anhydrase 1, and transport by solute carrier 4. Abstract: The freshwater monocot Ottelia alismoides is the only known species to operate three CO2 -concentrating mechanisms (CCMs): constitutive bicarbonate (HCO3 – ) use, C4 photosynthesis, and facultative Crassulacean acid metabolism, but the mechanism of HCO3 – use is unknown. We found that the inhibitor of an anion exchange protein, 4, 4'-diisothio-cyanatostilbene-2, 2'-disulfonate (DIDS), prevented HCO3 – use but also had a small effect on CO2 uptake. An inhibitor of external carbonic anhydrase (CA), acetazolamide (AZ), reduced the affinity for CO2 uptake but also prevented HCO3 – use via an effect on the anion exchange protein. Analysis of mRNA transcripts identified a homologue of solute carrier 4 (SLC4) responsible for HCO3 – transport, likely to be the target of DIDS, and a periplasmic α-carbonic anhydrase 1 (α-CA1). A model to quantify the contribution of the three different pathways involved in inorganic carbon uptake showed that passive CO2 diffusion dominates inorganic carbon uptake at high CO2 concentrations. However, as CO2 concentrations fall, two other pathways become predominant: conversion of HCO3 – to CO2 at the plasmalemma by α-CA1 and transport of HCO3 – across the plasmalemma by SLC4. These mechanisms allow access to a much larger proportion of the inorganic carbon pool and continued photosynthesis during periods of strong carbon depletion in productive ecosystems.